Batik Gallery And Workshop Design - Andri Nurjaman; Arief Perdana Putra; Andiyan Andiyan (Jurnal Arsitektur Archicentre, 2022)
Since ancient times, Indonesia has been known to have various kinds of batik spread in each region. Various motifs of batik culture are widespread throughout Indonesia, one of which is West Java. This type of West Java batik is widely known as Priangan batik and is used for various batik types in the West Java region. There are 16 batik-producing regions in West Java, each with its batik style. The Batik Gallery and Workshop design is an alternative space for existence and learning space about batik. The design of the Gallery and Batik Workshop is planned in Cipadung because there is a link between building function activities related to cultural arts and the selection of Neo Vernacular Architecture themes to represent Locality Architecture in buildings. The application of the theme will be implemented in the building in terms of mass, facade, and material. The Design of Batik Galleries and Workshops uses descriptive qualitative methods by collecting field data and looking for literature/comparative studies that will be used as references in the design process. It is hoped that the results of this design can be helpful for learning and valuable for readers in the future.